THE IMPACT OF PARENTAL SOCIALIZATION FACTORS TOWARDS FINANCIAL LITERACY OF UNDERGRADUATE STUDENTS IN BANDUNG - Nadya Putri, Gianina
Cashless society has been intensely promoted by the Indonesian Government from 2014 until now and will continue to develop it. By this, its people required to use the financial product. Financial products nowadays offer many varieties, and got advanced, should be parallel with the readiness of Indonesian citizens to prevent loss. Well-financial literacy should be prepared for these changes. However, looking at the current situation Indonesian in overall still have low financial literacy index compared to other country in Asia Pacific (Mastercard, 2015) thus it’s going to be government challenges in increasing the financial literacy of Indonesia to prepare for the more advances financial products. Financial literacy consists of some components such as financial knowledge, financial behaviour, and financial attitude (OECD, 2015). According to Chen and Volpe (1998) the score should at least 80% to be considered as having high financial literacy, where within the range between 60% - 80% considered as moderate level and below 60% is at the low level. The object for this research is undergraduate students who stayed in Bandung, Indonesia, as Bandung is one of the favorite destinations in Indonesia to pursue higher studies. The object choice due to the previous studies said that this phase is the first stage of parents guiding their undergraduate children to be independent in managing finance. Specifically, this research use discusses parents’ role as the primary agent of socialization. This research conduct interviews with parents to confirm the factors in parental socialization from previous studies. The previous studies said that the factors in parental financial socialization are money allowance, parents’ experience, financial communication, role modeling, and financial monitoring. However, from parents' point of view, it is said there are only money allowance, financial communication, and trust which they perform in socialization. They believe those factors matter in the socialization. Next, the author continues to conduct quantitative research by collecting a total of 204 samples of undergraduate students in Bandung, Indonesia. The questionnaire consists of financial literacy tests and statements regarding parental financial socialization. For the financial literacy level, the average score of undergraduate students in Bandung is 64%, where it lies on a moderate level. Another descriptive result, such as in gender it is shown that males have a higher average score with 67%, and the female group got 63%. Public university students got a slightly higher average score compared to private university students with the following order 65% and 64%. The same goes for the major of the students. Finance related majors got a slightly higher average score (65%) compare to the non-finance related major (64%). Through Multiple Linear Regression, we can conclude that the factors believed to help children in increasing their financial literacy level are money allowance and trust. Thus, parents should pay more attention to these factors and think carefully at determining the decision because it matters for the children's financial skills. This type of study should be further explored in future studies, given that there are still quite a few studies for the Indonesian context. The government also needs to create a literacy program that can engage parents and children.